Travel despite the COVID-19 pandemic: Implications for tourism recovery - Liu, Hongbo; Liu-Lastres, Bingjie; Zeng, Li; Donohoe, Holly (Frontiers in Psychology, 2022)
The COVID-19 pandemic has devastated the global tourism industry. This study explores why some Chinese residents travel during the pandemic. A mixed-methods research design was adopted, guided by the health belief model and relevant literature. Through 21 interviews with Chinese tourists who took an overnight leisure trip in May 2020, and a national survey among Chinese residents, this study explored factors influencing Chinese residents' travel-related decisions and behaviors during the pandemic. Results outline the influences of health beliefs, government trust, past travel experience, and psychological capital on tourists' risk-reduction behaviors. Theoretical and practical implications are provided regarding tourism recovery during pandemics.